WAYS TO EFFECTIVELY USE DOMESTIC INVESTMENT POTENTIAL IN THE NATIONAL ECONOMY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article highlights the scientific foundations for the effective use of domestic investment potential in the national economy, provides a methodology for assessing the use of domestic investment, analyzes the efficiency of capital and gives recommendations for the effective use of domestic investment.